2022
DOI: 10.31616/asj.2021.0106
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Endplate Changes Correlate with Presence of Cartilaginous Endplate in the Herniated Disc Tissue: Factor Predicting Failure of Conservative Treatment

Abstract: To characterize the scores of disc degeneration, inflammation, and nerve density in herniated disc samples and associate findings with the presence of vertebral endplate (VEP) changes on magnetic resonance imaging (MRI). Overview of Literature: Considering the role of disc composition in spontaneous regression and persistence of pain during conservative management, it is important to identify the influencing factors. VEP changes are highly associated with disc degeneration, but their correlation with herniated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
1
0
2
Order By: Relevance
“…Im gleichen Jahr zeigte ein systematisches Review der Literatur zu MC von 2001-2020 eine positive Evidenz für das intradiskale Vorhandensein von C. acnes in Kultur, Mikroskopie und Sequenzierung [14]. Endplattendefekte ("Schmorl-Knoten"), die in den Wirbelkörper eingebrochenem Bandscheibengewebe entsprechen, in den Fokus [16,25], die mit stärkerer Diskusdegeneration und Schmerz assoziiert scheinen [16,[24][25][26].…”
Section: Wieso Eigentlich Bakterien?unclassified
See 1 more Smart Citation
“…Im gleichen Jahr zeigte ein systematisches Review der Literatur zu MC von 2001-2020 eine positive Evidenz für das intradiskale Vorhandensein von C. acnes in Kultur, Mikroskopie und Sequenzierung [14]. Endplattendefekte ("Schmorl-Knoten"), die in den Wirbelkörper eingebrochenem Bandscheibengewebe entsprechen, in den Fokus [16,25], die mit stärkerer Diskusdegeneration und Schmerz assoziiert scheinen [16,[24][25][26].…”
Section: Wieso Eigentlich Bakterien?unclassified
“…Dabei unterschied sich nach Dr. Albert diese Gruppe bezüglich des hohen Ausmaßes an Schmerz und funktionellen Einschränkungen in Klinik und Anamnese von anderen Formen chronischer Rückenschmerzen, bei denen diese spezifischen MRT-Veränderungen nicht nachweisbar waren. Endplattendefekte ("Schmorl-Knoten"), die in den Wirbelkörper eingebrochenem Bandscheibengewebe entsprechen, in den Fokus [16,25], die mit stärkerer Diskusdegeneration und Schmerz assoziiert scheinen [16,[24][25][26].…”
unclassified
“…Coexisting facet joint-related pain, with nociception via the medial branch nerves is also possible, particularly given the frequency of disc height loss in patients with vertebrogenic pain, which results in greater facet joint loading at the spinal motion segment [ 31 ]. Indeed, it has been reported that Modic type 1 changes (MC1) and endplate defects commonly co-occur in patients with lumbar disc herniation and associated radiculopathy [ 32 , 33 ], and these findings are associated with higher rates of conservative treatment failure prior to discectomy [ 34 ]. In patients with LSS, endplate defects are a stronger predictor of axial LBP intensity than the severity of the spinal stenosis [ 35 ].…”
Section: Clinical Presentation Of Vertebrogenic Low Back Painmentioning
confidence: 99%